State-space estimation of ionospheric scintillation processes with a static GNSS receiver - Sousa, Fernando (2019)
The determination of the ionospheric scintillation processes that affect the reception of Global Navigation Satellite System (GNSS) signals is an important issue as it permits to monitor the ionosphere for practical and scientific applications and optimize the receiver performance in scintillation-prone scenarios using, for instance, a differential GNSS configuration. We propose an hybrid architecture for the receiver being constituted by a vector tracking block that estimates the receiver's clock drift coupled with an ensemble of extended Kalman filters driven by the prompt correlators that estimate the amplitude and phase of the fading processes. Those processes include as an important case the ionospheric scintillation.